Chronotropic Incompetence in Chronic Heart Failure: A State-of-the-Art Review. (August 2018) - Zweerink, Alwin; van der Lingen, Anne-Lotte C.J.; Handoko, M. Louis; van Rossum, Albert C.; Allaart, Cornelis P.
Abstract : Chronotropic incompetence (CI) is generally defined as the inability to increase the heart rate (HR) adequately during exercise to match cardiac output to metabolic demands. In patients with heart failure (HF), however, this definition is unsuitable because metabolic demands are unmatched to cardiac output in both conditions. Moreover, HR dynamics in patients with HF differ from those in healthy subjects and may be affected by β-blocking medication. Nevertheless, it has been demonstrated that CI in HF is associated with reduced functional capacity and poor survival. During exercise, the normal heart increases both stroke volume and HR, whereas in the failing heart, contractility reserve is lost, thus rendering increases in cardiac output primarily dependent on cardioacceleration. Consequently, insufficient cardioacceleration because of CI may be considered a major limiting factor in the exercise capacity of patients with HF. Despite the profound effects of CI in this specific population, the issue has drawn limited attention during the past years and is often overlooked in clinical practice. This might partly be caused by a lack of standardized approach to diagnose the disease, further complicated by changes in HR dynamics in the HF population, which render reference values derived from a normal population invalid. Cardiac implantable electronic devices (implantable cardioverter defibrillator; cardiac resynchronization therapy) now offer a unique opportunity to study HR dynamics and provide treatment options for CI by rate-adaptive pacing using an incorporated sensor that measures physical activity. This review provides an overview of disease mechanisms, diagnostic strategies, clinical consequences, and state-of-the-art device therapy for CI in HF.